Urea‐Catalysed Access to Novel Spirooxindole Benzopyrans via Domino Multicomponent Cascade: Approach Towards Sustainability. Issue 21 (6th June 2019) - Bagchi, Sourav; Shube Hussen, Abdulkadir; Deeksha,; Sharma, Anuj
Abstract: A multicomponent one‐pot domino reaction of 1‐hydroxy‐3 H ‐benzo[ f] chromen‐3‐one, isatin and malononitrile/ethyl cyanoacetate is herein investigated. The methodology concludes to synthesize diversified novel spiro‐benzo[ f ]pyranochromene derivatives in good to excellent yields. This method is compatible with different unsubstituted and substituted isatins bearing electron‐donating and electron‐withdrawing groups. The operational simplicity, short reaction time along with the gram scale up protocol make this synthetic process suitable for both academia as well as industry. Abstract : We have disclosed a urea catalysed greener, sustainable and efficient methodology to construct novel functionalized spiro‐benzo[ f ]chromenes under microwave irradiation in good to excellent yields. The reported protocol favors the gram scale synthesis and also free of tedious work up.